Nothing too much: reflecting about the role of contextualization in science teaching - de Freitas Dias de Souza, Karina Aparecida; Alves Cardoso, Arnaldo [UNESP] (Univ Autonoma Barcelona, 2010)
The contextualization and discussion about the science role in the social and economical development are unquestionably important for the science teaching process. It doesn't mean, however, that the scientific-theoretic knowledge and the strategies involved in its construction and application might be neglected. In this way, a dangerous situation is created when the contextualization is assumed as a unique and primordial target in science education. This paper presents a research carried out with 15 future chemistry teachers and the results show a worrying "supervalorization", of the contextualization beside other equally important aspects of the chemical knowledge.
Keywords: Teachers' training; contextualization; scientific literacy; epistemology; science teaching